TEST OF LIGNIN AND CELLULOSE DECOMPOSITION AND PHOSPHATE SOLUBILIZATION BY SOIL FUNGI OF GUNUNG HALIMUN - Suciatmih, Suciatmih (Research Center for Biology-Indonesian Institute of Sciences, 2001)
In order to know the capability of lignin and cellulose degradation and phosphate solubilization by soil fungi of Gunung Halimun National Park, a study was carried out to qualitatively analyse its physiological properties. Out of 35 soil fungi tested, 1 species that belonged to Basidiomycetes degraded lignin, 32 species degraded cellulose, and 31 species dissolved inorganic phosphate.The presence of soil fungi that degraded cellulose and dissolved phosphate could be used as a candidate for biotechnology application as well as to increase soil fertility.